Noise and interference reduction in amplitude modulation - Borochov, Amos (My University, 2016)
Amplitude modulation, is the oldest modulation technique used for voice communication.It is the simplest and cheapest way to modulate and demodulate voice, and as a result, it did not lose much popularity in spits of the development of other, more efficient modulation technique. This project offers a new approach for AM demodulation. The two sidebands are separated and divided into many su-bands. The signals with the lowest noise level are solected and thier levels are individually adjusted according to signal conditions. The result is reduction of over 35 dB in continuous interference and about 15 dB in whit noise level. The new detector and about out-performs the conventional detectors in all aspects and can be used in applications where top performance is required and where mone is no object.
A project report sUbmitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering. Sandtoh, 1995.
Keywords: Radio--Research; Amplitude modulation; Amplitude modulation detectors